2018
DOI: 10.1097/bot.0000000000001177
|View full text |Cite
|
Sign up to set email alerts
|

Split-Depressed Lateral Tibial Plateau Fractures: A Comparison of Augmented Percutaneous Screws Versus Augmented Plate and Screw Construct in a Cadaveric Model

Abstract: Objectives: To compare the strength of fixation of percutaneous screw versus plate/screw fixation in a paired cadaver model of OTA 41-B3 (Schatzker type II) split-depression fractures of the lateral tibial plateau. Methods: Six matched pairs of cadaveric knees were acquired. An OTA 41-B3 (Schatzker type II) split-depression fracture was created in all specimens using a standardized method. One specimen from each matched pair of knees was fixed with perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A recent cadaver study demonstrated that the use of independent screws for fixation provides comparable strength relative to plate and screw constructs, and this technique may be particularly beneficial in that it allows for less invasive treatment of TPF. 77 Schatzker III pure depression type fractures of the lateral plateau most often occur in the setting of poor bone quality. Treatment of these fractures involves elevation of the depression and restoration of normal plateau architecture.…”
Section: Treatmentmentioning
confidence: 99%
“…A recent cadaver study demonstrated that the use of independent screws for fixation provides comparable strength relative to plate and screw constructs, and this technique may be particularly beneficial in that it allows for less invasive treatment of TPF. 77 Schatzker III pure depression type fractures of the lateral plateau most often occur in the setting of poor bone quality. Treatment of these fractures involves elevation of the depression and restoration of normal plateau architecture.…”
Section: Treatmentmentioning
confidence: 99%
“…As CaPO4 augmentation has become commonplace, some surgeons have explored its use in constructs that may be inadequate without augmentation. Bowles et al 52 performed a cadaver evaluation of two augmented constructs for OTA 41-B3 split depression (Schatzker type II) fractures. The authors compared two 6.5-mm cannulated lag screws to a 4.5-mm proximal tibial plate and cancellous lag screws.…”
Section: Calcium Phosphatementioning
confidence: 99%
“…A thorough knowledge of anatomy is required for adequate reconstruction, early mobilization and to prevent long term complications [6]. Fixation of these fractures can be done through conventional or minimally invasive arthroscopic aided methods [7][8][9]. Anterolateral approach along with lateral buttress plating is used generally [10,11].…”
Section: Introductionmentioning
confidence: 99%